Faktor Yang Mempengaruhi Peningkatan Tekanan Darah Pada Lansia Di Panti Sosial Tresna Werdha Banyuwangi - Hendrik Probo Sasongko (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Hypertension is often referred to as "The Silent Killer" because generally sufferers are not aware that they have high blood pressure, and only find out about it after complications occur. The aim of this research is to find out what risk factors influence increased blood pressure in the elderly at UPTmPSTW Banyuwangi.. This research was conducted using a quantitative research approach through surveys and primary data collection. The sample population consists of elderly people aged 60 years and over.. The results of the Chi Square analysis test for the three factors obtained a p-value for each factor, namely the BMI factor (nBody Mass Index) with a value of p=n0.018, the family history factor with a value of p=n0.008, the physical activity factor with a value of p=n0.014. it can be concluded that all three factors have a relationship with hypertension and the most dominant factor is BMI (Body Mass Index) with a value (nb/regression coefficient) of 0.153. The BMI factor (nBody Mass Index) appears as the most dominant factor contributing to the incidence of hypertension in the elderly. Therefore, special attention must be given to weight management and diet in the elderly as an effective preventive measure.